Severe hypercalcemic hyperparathyroidism developing in a patient with hyperaldosteronism and renal resistance to parathyroid hormone. (15th February 2013) - Park‐Sigal, Jennifer; Don, Burl R; Porzig, Anne; Recker, Robert; Griswold, Virginia; Sebastian, Anthony; Duh, Quan‐Yang; Portale, Anthony A; Shoback, Dolores; Schambelan, Morris
Abstract We evaluated an African American woman referred in 1986 at age 33 years because of renal potassium and calcium wasting and chronic hip pain. She presented normotensive, hypokalemic, hypocalcemic, normophosphatemic, and hypercalciuric. Marked hyperparathyroidism was evident. Urinary cyclic adenosine monophosphate (cAMP) excretion did not increase in response to parathyroid hormone (PTH) infusion, indicating renal resistance to PTH. X‐rays and bone biopsy revealed severe osteitis fibrosa cystica, confirming skeletal responsiveness to PTH. Renal potassium wasting, suppressed plasma renin activity, and elevated plasma and urinary aldosterone levels accompanied her hypokalemia, suggesting primary hyperaldosteronism. Hypokalemia resolved with spironolactone and, when combined with dietary sodium restriction, urinary calcium excretion fell and hypocalcemia improved, in accord with the known positive association between sodium intake and calcium excretion. Calcitriol and oral calcium supplements did not suppress the chronic hyperparathyroidism nor did they reduce aldosterone levels. Over time, hyperparathyroid bone disease progressed with pathologic fractures and persistent pain. In 2004, PTH levels increased further in association with worsening chronic kidney disease. Eventually hypercalcemia and hypertension developed. Localizing studies in 2005 suggested a left inferior parathyroid tumor. After having consistently declined, the patient finally agreed to neck exploration in January 2009. Four hyperplastic parathyroid glands were removed, followed immediately by severe hypocalcemia, attributed to "hungry bone syndrome" and hypoparathyroidism, which required prolonged hospitalization, calcium infusions, and oral calcitriol. Although her bone pain resolved, hyperaldosteronism persisted. © 2013 American Society for Bone and Mineral Research.